Observations of fluorescent aerosol–cloud interactions in the free troposphere at the High-Altitude Research Station Jungfraujoch - I. Crawford; G. Lloyd; G. Lloyd; E. Herrmann; C. R. Hoyle; C. R. Hoyle; K. N. Bower; P. J. Connolly; M. J. Flynn; P. H. Kaye; T. W. Choularton; M. W. Gallagher (Atmospheric Chemistry and Physics, 2016)
The fluorescent nature of aerosol at a high-altitude Alpine site was studied using a wide-band integrated bioaerosol (WIBS-4) single particle multi-channel ultraviolet – light-induced fluorescence (UV-LIF) spectrometer. This was supported by comprehensive cloud microphysics and meteorological measurements with the aims of cataloguing concentrations of bio-fluorescent aerosols at this high-altitude site and also investigating possible influences of UV–fluorescent particle types on cloud–aerosol processes. Analysis of background free tropospheric air masses, using a total aerosol inlet, showed there to be a minor increase in the fluorescent aerosol fraction during in-cloud cases compared to out-of-cloud cases. The size dependence of the fluorescent aerosol fraction showed the larger aerosol to be more likely to be fluorescent with 80 % of 10 μm particles being fluorescent. Whilst the fluorescent particles were in the minority (NFl∕NAll  =  0.27 ± 0.19), a new hierarchical agglomerative cluster analysis approach, Crawford et al. (2015) revealed the majority of the fluorescent aerosols were likely to be representative of fluorescent mineral dust. A minor episodic contribution from a cluster likely to be representative of primary biological aerosol particles (PBAP) was also observed with a wintertime baseline concentration of 0.1 ± 0.4 L−1. Given the low concentration of this cluster and the typically low ice-active fraction of studied PBAP (e.g. pseudomonas syringae), we suggest that the contribution to the observed ice crystal concentration at this location is not significant during the wintertime.